A Device for the Functional Evaluation of the VOR in Clinical Settings - Ramat, Stefano; Colnaghi, Silvia; Böhler, Andreas; Astore, Serena; Falco, Paola; Mandalà, Marco; Nuti, Daniele; Colagiorgio, Paolo; Versino, Maurizio (Frontiers in Neurology, 2012)
The experimental assessment of the vestibulo-ocular-reflex (VOR) gain provides an objective and quantitative measure of VOR performance which is nonetheless difficult to correlate with its efficiency in everyday living conditions. We developed the Head Impulse Testing Device (HITD) based on an inertial sensing system allowing to investigate the functional performance of the VOR by testing its gaze stabilization ability in response to head impulses at different head angular accelerations. HITD results on a population of 39 vestibular patients were compared to those of 22 controls. Overall the sensitivity of the HITD was 92% against the results of the clinical head impulse test and 83% against the clinical diagnosis, while the specificity was 58% against the clinical head impulse test and 83% against the diagnosis. The HITD appears to be a very promising tool for detecting abnormal VOR performance while providing information on the functional performance of the rotational VOR. As compared to the usual testing devices the HITD tests higher frequencies and accelerations that characterize head movements in everyday life activities and provides a functional assessment that is more likely to be related to the subject’s self-feeling.